Pengaruh Kualitas Produk, Citra Merek dan Gaya Hidup terhadap Keputusan Pembelian Smartphone Iphone: - Febrianty, Ellinda; Pudjoprastyono, Hery; Ariescy, Reiga Ritomiea (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to determine the effect of product quality, brand image, and lifestyle on the purchase decision of an Iphone Smartphone. This research method uses quantitative methods. Variable measurement uses a likert scle with a vulnerability scaleof 1-5 through a google form questionnaire distributed to repondents. The population in this study were all 2019. FEB UPN East Java Veterans Students currently using or have used an iPhone. Sampling using proportional stratified random sampling and probability sampling. 100 students have a referee. Partial least squares (PLS) analysis was used to process the data. The results show that factors such as product quality, brand image and lifestyle have a positive and significant influence on the iPhone smartphone purchase decision of the East Java FEB UPN "Veteran" students of the year 2019. Keywords: Product Quality, Brand Image, Lifestyle, Purchase Decision